Evaluation of Alterations in Nutrient Utilization and Intestinal Health in Response to Heat Stress in Pekin Ducks Based on a Pair-Feeding Experimental Design - Xiangyi Zeng; Arshad Javid; Gregory S. Fraley; Gang Tian; Keying Zhang; Shiping Bai; Xuemei Ding; Jianping Wang; Yan Liu; Yue Xuan; Shanshan Li; Qiufeng Zeng (Animals)
The objective of this study was to investigate alterations in nutrient utilization, standardized ileal digestibility of amino acids (SIDAA), and intestinal health in response to heat stress (HS) in Pekin ducks. A total of 240 healthy 28-day-old male Pekin ducks were randomly allocated to three groups: a normal control (NC) group, an HS group, and a pair-fed (PF; provided an amount of feed equal to that consumed by the HS group to eliminate the effects of feed intake) group, each with eight replicate cages of ten birds. The results showed that HS significantly reduced the apparent utilization of dietary energy, ether extract, and crude protein compared to both the NC and PF groups (p < 0.05), but yielded comparable SIDAA to the PF group. The HS group exhibited reduced mRNA levels of EAAT3 and PepT1, along with elevated mRNA levels of CAT1, GLUT5, and FATP6 in the jejunum compared to the NC or PF groups, respectively (p < 0.05). Furthermore, HS resulted in a significant deterioration of jejunal morphology and goblet cell count compared to the NC and PF groups (p < 0.05). Serum fluorescein isothiocyanate-dextran levels were significantly higher in HS ducks than in NC ducks (p < 0.05), but did not differ from PF ducks. At order-level classification of ileal mucosal microbiota, HS markedly increased the relative abundance of Bacillales, Deferribacterales, and Actinomycetales versus NC (p < 0.05), while significantly decreasing Bifidobacteriales abundance relative to PF (p < 0.05). Collectively, HS induces a leaky gut and microbiota dysbiosis that compromises gut health, thereby reducing dietary nutrient utilization in Pekin ducks. The observed reduction in feed intake constitutes a primary driver of intestinal health deterioration in heat-stressed Pekin ducks.